Pemahaman HAM dan Respon Mahasiswa Sekolah Tinggi Keagamaan Katolik terhadap Isu-isu Sensitif - Metoddyus Tri Brata Role; Subandri Simbolon (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
This article aims to examine the understanding of Catholic Religion teachers’ candidates on the implementation of human rights in their relation to human rights issues such as gender, ideology, and religious minorities. The questions are: first, to what extent do students understand human rights and how do they apply that understanding in approaching human rights issues? Second, how do they transfer the understanding they have especially if those understandings are linked to the Church's views that are closely related to these issues? These questions were analyzed by qualitative research using open-ended questionnaires and semi-structured interviews. From the results of data processing, it was found that the students had an understanding of human rights and implemented that understanding in their relations with groups of different religions with an attitude of tolerance, acceptance of differences and respect. However, with regard to sensitive issues such as gender, banned political parties or organizations and Local Religion, they still use textual understandings. The main reason is that they rarely come face to face with those who have this gender identity, ideology and religion. Another factor is their lack of understanding of the inclusive view of the Church on these issues. Finally, the detailed implication and research suggestions are included necessary to accommodate meeting spaces to raise the spirit of humanity (through which principles of human rights, especially Freedom of Religion and Belief, are promoted) that is much more inclusive and offer more inclusive interpretations and attitudes of the Catholic Church towards these issues.by peer scholars, especially in the same field of research